Somatostatin-containing protein-based drug in the treatment of infertility: efficacy evaluation using a leuprorelin-induced spermatogenesis impairment model in male rats - A. A. Matichin; K. L. Kryshen; A. A. Matichina; N. M. Faustova; Ya. A. Gushchin; M. N. Makarova; V. V. Reshetnik; G. T. Sukhikh; S. M. Yudin; V. G. Lunin (Вестник урологии, 2025)
Introduction. A novel drug based on a somatostatin-containing protein is being developed for use in female and male infertility to increase the reproductive capacity, activate ovarian reserve follicles and their entry into the growth phase, accelerate the growth of resting follicles, increase the volume of ejaculate and improve the sperm quality characteristics.Objective. To evaluate the efficacy of a somatostatin-containing protein-based drug in a rat model of spermatogenesis disorder induced by a single injection of 600 µg/kg leuprorelin.Materials & methods. The study evaluated several factors, including microscopic changes in testicular tissue, mass ratios of reproductive organs (testes, epididymis, seminal vesicles), semen parameters, and serum testosterone and somatotropin levels.Results. It was demonstrated that in the context of gonadotropin reduction and subsequent testosterone decline resulting from prolonged exposure to leuprorelin, the tested preparation, comprising a somatostatin-containing protein in a dosage range of 10 to 250 µg/kg, led to an increase in somatotropin and testosterone levels and the normalization of the spermatogenesis process. It was observed that the studied preparation resulted in a notable elevation in the concentration and proportion of motile spermatozoa.Conclusion. The obtained results are consistent with previously published data demonstrating improved spermatogenesis parameters following administration of exogenous somatotropic hormone in animal models. This allows us to hypothesize a potential mechanism of action for the tested drug, namely the synthesis of specific autoantibodies against somatostatin and subsequent blockade of its activity, which in turn leads to increased endogenous levels of somatotropic and sex hormones in the organism.